Novel Coronavirus (COVID-19): A New Emerging Pandemic Threat - Rezabakhsh, Aysa; Ala, Alireza Reza; Khodaei, Sepideh Hassanpour (Tabriz University of Medical Sciences, 2020)
Coronavirus disease 2019 (COVID-19), with high-transmission power, is spreading rapidly, and researchers are endeavoring to discover eligible medications for its efficacious prevention and treatment globally. According to the World Health Organization (WHO) reports, several multicenter clinical trials are launched to determine effective treatment protocols against COVID-19-associated pneumonia. In this article, we aimed to discuss some critical issues concerning novel coronavirus. © 2020 The Author(s).
Keywords: 2019-nCoV; COVID-19; Novel Coronavirus; Pneumonia; SARS-CoV-2